Menggagas Kampus Islam yang Unggul Melalui Penerapan Blue Ocean Strategy : (Studi di STAIS Dharma Segeran Indramayu) - Arwani Arwani (Khulasah : Islamic Studies Journal, 2019)
This paper aims to find alternative solutions towards superior educational institutions by applying the concept of Blue Ocean Strategy (BOS). Blue Ocean Strategy is defined as a blue ocean strategy by Kim & Mauborgne (2014): “Blue oceans strategy are defined by untapped market space, demand creation, and the opportunity for highly profitable growth”. Blue Ocean Strategy is how to create unexplored market space, which can create demand and provide highly profitable growth opportunities. In essence, how to compete with agile in the competition; how to cleverly read the competition, develop a systematic strategy and framework to create an unlimited market. The method used in the implementation of this research is a qualitative method and is a photo shoot of phenomena that occur in the field, through observation, documentation studies and interviews with interested parties in the STAIS Dharma Segeran Indramayu environment. Based on the results of data capture in the analysis of the implementation of the blue ocean strategy using the erase-reduce-increase-create scheme and the strategy canvas, based on the principle of the blue ocean strategy, namely to innovate value by increasing the value of benefits while reducing costs. In this case, STAIS Dharma Segeran Indramayu creates a value curve by innovating by improving the quality of good service and improving product quality with the support of a strong reason, namely eliminating the high price aspect. The brand image of STAIS Dharma Segeran Indramayu itself also supports the creation of a value curve. The results of the study also looked at the position of STAIS Dharma Segeran Indramayu in the blue ocean area where STAIS Dharma Segeran Indramayu was carrying out a blue ocean strategy based on analysis using a strategy canvas.